IMPLEMENTASI STRATEGI PADA PENGEMBANGAN WISATA DIENG KABUPATEN BANJARNEGARA - Nurlaili Restiana; Denok Kurniasih; Muslih Faozanudin (The Indonesian Journal of Public Administration (IJPA), 2017)
Abstract: The development of the tourism sector is very important, especially for the District of Banjarnegara in the area of ​​Tourism Dieng which is a natural tourist area that attracted many visitors. Tourism sector is the main sector of the economy of Banjarnegara Regency, but tourism development of Banjarnegara Regency also raises obstacles, so that tourism development effort needs to be done with and appropriate strategy. The research method used is qualitative method, with technique of selecting informant purposive sampling. From the result of the research, it is known that Implementation of development strategy of Dieng tourism area in Banjarnegara regency generally has been running well enough seen from 3 (three) aspects ie program, resources, and procedure. Researchers found that the development program of tourism destinations and technological resources capable of supporting the development of tourism Dieng. But there are still shortcomings in the aspect of resources, namely financial resources are still limited from the budget and there are still inadequate physical resources. Keywords: Strategy Implementation, Tourism Development, Nature Tourism  Abstrak: Pembangunan sektor pariwisata sangat penting, khususnya untuk Kabupaten Banjarnegara pada kawasan Wisata Dieng yang merupakan kawasan wisata alam yang cukup diminati banyak pengunjung. Sektor pariwisata menjadi sektor unggulan perkonomian Kabupaten Banjarnegara, namun pembangunan pariwisata Kabupaten Banjarnegara juga memunculkan kendala, sehingga upaya pengembangan pariwisata perlu dilakukan dengan dan strategi yang tepat. Metode penelitian yang digunakan adalah metode kualitatif, dengan teknik pemilihan informan purposive sampling. Dari hasil penelitian diketahui bahwa Implementasi strategi pengembangan kawasan wisata Dieng di Kabupaten Banjarnegara secara umum sudah berjalan dengan cukup baik dilihat dari 3 (tiga) aspek yaitu program, sumber daya, dan prosedur. Peneliti menemukan bahwa program pengembangan destinasi pariwisata dan sumber daya tekhnologi mampu mendukung pengembangan wisata Dieng. Namun masih ada kekurangan dalam aspek sumber daya yaitu sumber daya keuangan masih terbatas dari APBD dan masih ada sumber daya fisik yang belum memadai. Kata kunci: Implementasi Strategi, Pengembangan Pariwisata, Wisata Alam